Jakarta Islamic Index (JII) Financial Performance Analysis Using EVA and MVA Methods - Acep R. Jayaprawira; Sulistyandari; Alum Kusumah (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Purpose – The study aims to examine the financial performance of firms listed on the Jakarta Islamic Index between 2018 and 2020 using the Economic Value Added (EVA) and Market Value Added (MVA) methods. Methodology/approach – The study is a descriptive quantitative study with the population is all companies listed on the Jakarta Islamic Index in 2028-2020. The purposive sampling method employed and determined the sample of seven companies. The data gained from the company's financial statements, accessed at www.IDX.co.id. Findings – According to the findings of this study, the company's financial performance using the EVA method is positive (EVA>0), indicating that the company can generate economic value added. With a positive number (MVA>0), the financial performance of the MVA is similarly good. It signifies that the company can generate market value-added and has managed to expand investor wealth. Novelty/value – The concept of measuring financial performance based on Value-added (economic value added - EVA and Market Value added - MVA) to overcome the limitations of financial ratio analysis. These concepts are crucial indicators of an investment's ability to create wealth. By using EVA and MVA, this study examined the financial performance of companies listed on the Jakarta Islamic Index.